Hydrographic and ecologic implications of foraminiferal stable isotopic response across the U.S. mid‐Atlantic continental shelf during the Paleocene‐Eocene Thermal Maximum. (21st January 2017) - Makarova, Maria; Wright, James D.; Miller, Kenneth G.; Babila, Tali L.; Rosenthal, Yair; Park, Jill I.
Abstract: We present new δ 13 C and δ 18 O records of surface ( Morozovella and Acarinina ) and thermocline dwelling ( Subbotina ) planktonic foraminifera and benthic foraminifera ( Gavelinella, Cibicidoides, and Anomalinoides ) during the Paleocene‐Eocene Thermal Maximum (PETM) from Millville, New Jersey, and compare them with three other sites located along a paleoshelf transect from the U.S. mid‐Atlantic coastal plain. Our analyses show different isotopic responses during the PETM in surface versus thermocline and benthic species. Whereas all taxa record a 3.6–4.0‰ δ 13 C decrease associated with the carbon isotope excursion, thermocline dwellers and benthic foraminifera show larger δ 18 O decreases compared to surface dwellers. We consider two scenarios that can explain the observed isotopic records: (1) a change in the water column structure and (2) a change in habitat or calcification season of the surface dwellers due to environmental stress (e.g., warming, ocean acidification, surface freshening, and/or eutrophication). In the first scenario, persistent warming during the PETM would have propagated heat into deeper layers and created a more homogenous water column with a thicker warm mixed layer and deeper, more gradual thermocline. We attribute the hydrographic change to decreased meridional thermal gradients, consistent with models that predict polar amplification. The second scenario assumes that environmental change was greater in the mixed layer forcing surface dwellers to descend into thermocline waters as a refuge or restrict their calcification to the colder seasons. Although both scenarios are plausible, similar δ 13 C responses recorded in surface, thermocline, and benthic foraminifera challenge mixed layer taxa migration. Key Points: Sediments from the U.S. mid‐Atlantic margin capture thick shelf records of the PETM Foraminiferal isotopic records from NJ cores show different responses in surface versus deep taxa Isotopic trends are interpreted to reflect changes in bloom season and/or in shelf hydrography